The Effects of Land Use and Landscape Position on Soil Physicochemical Properties in a Semiarid Watershed, Northern Ethiopia - Weldemariam Seifu; Eyasu Elias; Girmay Gebresamuel (Applied and Environmental Soil Science)
Understanding topography effects and assessing the soil properties in different land use is an essential first step for sustainable soil management. Hence, land use type and altitudinal gradient on selected soil parameters were studied in Ayiba watershed, northern Ethiopia. Thirty composite soil samples were collected from 0 to 30 cm of soil depth under four land use types across three altitudinal gradients and were analyzed for selected soil parameters following the standard procedures. A significant main effect of land use and altitudinal gradient on the content of the soil particles was noted. Results also indicated that the bulk density (BD), total porosity (TP), and Pav of the soil are significantly different (p < 0.05) in the watershed because of land use type and altitudinal gradient. Barren land and higher altitude landscapes have the highest BD, and the lowest TP, and grassland and lower altitude landscapes have the lowest BD and high TP. Intensive cultivation accompanied by natural land conversion and erosion due to the rugged landscape nature caused high BD and low TP. Analysis of variance results also shows the significant interaction effect of land use type and altitudinal gradient on EC, SOM, SOC (p < 0.001), and pH-water (1:2.5), and TN (p < 0.01). The Pearson correlation of SOM with TP, TN, MC, and clay content showed a strong positive relationship. But, SOC, TN, and clay content were negatively correlated with BD. Soils of the study watershed are found in low to optimum rating levels in their selected physicochemical properties. Overall, the results show that land use and topography gradient significantly affected soil physicochemical properties in the study watershed. Therefore, soil management options should focus on scenarios that could improve the soil conditions to enhance crop production on a sustainable basis.